Modifiable risk factors for permanent pacemaker after transcatheter aortic valve implantation: CONDUCT registry. Issue 1 (7th February 2023) - Rudolph, Tanja; Droppa, Michal; Baan, Jan; Nielsen, Niels-Erik; Baranowski, Jacek; Hachaturyan, Violetta; Kurucova, Jana; Hack, Luis; Bramlage, Peter; Geisler, Tobias
Abstract : Objective: The onset of new conduction abnormalities requiring permanent pacemaker implantation (PPI) after transcatheter aortic valve implantation (TAVI) is still a relevant adverse event. The main objective of this registry was to identify modifiable procedural risk factors for an improved outcome (lower rate of PPI) after TAVI in patients at high risk of PPI. Methods: Patients from four European centres receiving a balloon-expandable TAVI (Edwards SAPIEN 3/3 Ultra) and considered at high risk of PPI (pre-existing conduction disturbance, heavily calcified left ventricular outflow tract or short membranous septum) were prospectively enrolled into registry. Results: A total of 300 patients were included: 42 (14.0%) required PPI after TAVI and 258 (86.0%) did not. Patients with PPI had a longer intensive care unit plus intermediate care stay (65.7 vs 16.3 hours, p<0.001), general ward care stay (6.9 vs 5.3 days, p=0.004) and later discharge (8.6 vs 5.0 days, p<0.001). Of the baseline variables, only pre-existing right bundle branch block at baseline (OR 6.8, 95% CI 2.5 to 18.1) was significantly associated with PPI in the multivariable analysis. Among procedure-related variables, oversizing had the highest impact on the rate of PPI: higher than manufacturer-recommended sizing, mean area oversizing as well as the use of the 29 mm valve (OR 3.4, 95% CI 1.4 to 8.5, p=0.008) all were significantly associated with PPI. Rates were higher with the SAPIEN 3 (16.1%) vs SAPIEN 3 Ultra (8.5%), although not statistically significant but potentially associated with valve sizing. Implantation depth and postdelivery balloon dilatation also tended to affect PPI rates but without a statistical significance. Conclusion: Valve oversizing is a strong procedure-related risk factor for PPI following TAVI. The clinical impact of the valve type (SAPIEN 3), implantation depth, and postdelivery balloon dilatation did not reach significance and may reflect already refined procedures in the participating centres, giving attention to these avoidable risk factors. Trial registration number: NCT03497611 .